The Extent of Science Teachers' Practice of Analyzing Results of Achievement Tests and its Relationship to their Attitudes towards it - Waleed Al Nawafleh; Ali Al Omari; Razan Al Mohaidat (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
The study aims to identify the degree of science teachers' practice of analyzing the results of achievement tests and its relationship to their attitudes towards tests. To achieve the objectives of the study, two tools were developed and used: the first tool was a scale of science teachers' practice of analyzing the results of achievement tests, and the second tool was a questionnaire about science teachers' attitudes towards achievement tests. The two tools were applied to a sample of (221) male and female science teachers in the districts of Kasbah Irbid and Liwa Bani Obeid. The results of the study showed that the degree of science teachers' practice of analyzing the results of achievement tests was low. There was a significant difference in that degree attributed to educational qualification in favor of teachers who hold an educational qualification. There are no significant differences in the teachers' attitudes due to the effect of gender or teacher's years of experience. There was a significant difference attributed to educational qualification in favor of teachers who hold an educational qualification. The results also indicated the existence of a significant correlation between the degree of science teachers' practice of analyzing the results of achievement tests and their attitudes towards it.